Lightweight methane-air gas turbine controller and simulator - Odi Fawwaz Alrebei (17562522) (2022)
Due to the uncertainties of determining stable, efficient, and safe operating conditions of methane-air gas turbines and the complexity of involving multivariable parameters, the task of controlling and analyzing methane-gas turbines remains a challenge despite the existing methods of control and analyses in the literature. In fact, as far as the methane-air gas turbines are concerned, there is still much room for improvement within the criterion of (computation effort, settle time, its capacity to adjust with a variable range of set-points, as well as its stable, steady, and dynamic outputs can all be enhanced). Furthermore, an accurate system-identification phase has been adopted in this paper to initiate the process of advancing an efficient gas turbine controller by determining the system's sensitivities towards the involved multivariable parameters. Therefore, this paper presents a control and analysis tool for methane-air gas turbines. This tool is a ‘light code (the time to reach the desired set-point (i.e., settle period reaches 1 s)) to serve as a methane-air gas turbine controller that can be used for experimentation or applied on an industrial scale. Moreover, the code is designed with a user interface that enables the simulations and system identification for the methane-fueled gas turbine, thus; ensuring that the governing parameters are calibrated precisely. The code was created using LabVIEW and GASEQ and is driven by conventional gas turbine cycle assessments. A simulation case study has been utilized as a system identification phase to determine the system's sensitivity of temperatures and works at the three primary stages of a simple cycle methane-air gas turbine (compressor, combustion chamber, and turbine) toward the multivariable input parameters of the compression stage (compressor pressure ratio, efficiency, inlet pressure, and temperature), the combustion phase (methane, airflow rates) and the expansion phase (turbine ratio of pressures and isentropic efficiency). Based on the sensitivity analysis performed through the developed code, the turbine output temperature is shown to be very sensitive to the turbine's parameters ( P 04 / P 03 and ε t ). This essentially emphasizes the possibility of including waste heat utilization mechanisms (i.e., heat exchangers, combined cycles) for turbines with high P 04 / P 03 or/and low ε t , resulting in a high turbine outlet temperature. Based on the performed system identification phase and sensitivity analyses, the intervals of the Proportional controller gain ( K c ) , Integral time ( t i ) , and Derivative time ( t d ) have been identified to guarantee a settling period ( T s ) within [1 s-60 s] to achieve the desired temperature set-point which eliminates turbine overheating. Other Information Published in: Energy Conversion and Management: X License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecmx.2022.100242